Design Review as a Powerful Tool to Address Human Factors: A Collaborative Approach. Issue 3 (2nd July 2020) - Brehm, Eric; Hertle, Robert
Abstract: Human error is the major cause of structural collapse. Design review, together with execution control, is the most effective way to remove human errors from the building process and therefore most societies have procedures for design review and execution control installed. These systems work differently, e.g. preventive or repressive, and consequently affect the involved parties differently. In this paper, the effect of different design review and execution control systems on the acting engineer as an individual will be assessed by addressing human factors that influence design decisions. The paper will focus on the structural design engineer and the benefits of a well-tuned collaboration between the design engineer and the design review engineer, who also performs on-site inspections. The goal is to provide a better understanding of the impact of the design review and execution control procedure on the individual as well as on the development of the project. Human factors affect the design engineer subconsciously and influence the decision making in a significant way. Awareness of these factors and the corresponding influence due to the design review and execution control system will improve the design outcome and the relationship between the design engineer and design review engineer.